Renewable Energy, Private Sector Development, and CO2 Emissions: Evidence from Early Demographic Dividend Countries - Nigmatullaeva, Gulchekhra; Ibragimova, Farangiz; Dekhkanova , Nargiza; Umarov, Abdusalom; Sadikov, Avazbek (International Journal of Energy Economics and Policy, 2025)
The aim of this study is to examine the relationship between renewable energy and CO2 emissions across 48 early demographic dividend countries over the period 2000-2020. The contribution of this study is many-fold. First, ours is the first study to assess the effect of RES on CO2e while controlling for conventional predictors of environmental degradation. Second, we also examine the role of new business density on CO2 emissions. Using various panel data estimation techniques such as Ordinary Least Squares (OLS), OLS with time fixed effects, Fixed Effects (FE) estimation, Panel- Corrected Standard Errors (PCSE), Generalized Least Squares (GLS), two-step system GMM estimator we find that renewable energy and private sector development mitigate CO2 emissions. For instance, one standard deviation increase in renewable energy consumption is associated with 1.4% decrease in per capita CO2 emissions. Governments should implement policies that encourage investment in renewable energy, such as tax incentives, subsidies, and public-private partnerships, to accelerate the decarbonization process. Second, promoting entrepreneurship and private sector growth through regulatory reforms and access to finance can contribute to environmental sustainability by fostering innovation in green technologies and resource-efficient business practices.